Antihypertensive effects of pentacyclic triterpenoid from Convolvulus pluricaulis and its plausible mechanism of action hypothesizing its selectivity targeting Mineralocorticoid receptor of RAAS. - Kanagasabai Somarathinam; Seshan Gunalan; Ananthasri Sailapathi; Dharani Amirtha Metilda A; Balashanmugam Pannerselvam; M. Mohanasundari; Ashok Kumar Balaraman; Gugan Kothandan (Elsevier, 2023)
Background: The renin-angiotensin-aldosterone system (RAAS) is important in maintaining blood pressure and malfunction of this system leads to the main cause of hypertension. Though a variety of synthetic inhibitors have been used to treat hypertension and related disorders, chronic use of these inhibitors causes undesirable side effects. To eliminate this problem, several scientific studies have proved that plant based and food derived products could be used as an alternative strategy to treat high blood pressure. Purpose: We intend to isolate the major bioactive compound from the medicinal plant Convolvulus pluricaulis as it is reported to possess anti-hypertensive activity. We also aimed to address the mechanism of action of taraxerol and to hypothesize its selectivity targeting RAAS. Study design: The study was designed to isolate the phytoconstituent from C. pluricaulis and characterization by XRD, NMR, FT-IR, and UV-Vis. To further elucidate the activity of isolated molecules, we have designed a two-way approach using in-silico and in-vitro methodologies. Methods: The roots of Convolvulus pluricaulis were dried, powdered and the extract was purified by repeated column chromatography. The purified compound was characterized by UV-Vis, IR, NMR, and single crystal X-ray diffraction. The high quality single crystal was grown from the mixture of hexane ethyl acetate. Molecular docking was done to identify the interaction pattern and binding efficacy of isolated compounds against various receptors of RAAS and the stability of the molecule was analyzed by molecular dynamic simulations. The cytotoxicity of the molecule was checked using the MTT assay and the IC50 value was also calculated against the AngII-induced cardiac hypertrophy in H9c2 cells. Tanimoto coefficient was calculated to check the similarity indices with the already reported antihypertensives from plants/herbs. Results: The crystal structure of taraxerol solved by crystallography has been deposited with the Cambridge Crystallographic Data Centre (CCDC: 2,180,265). Taraxerol had an IC50 at 20 μM concentration against AngII-induced cardiac hypertrophy in H9c2 cells, indicating that it suggestively increased the cell viability as compared to positive control. In-silico molecular docking analysis of taraxerol found that taraxerol binds to mineralocorticoid receptor with the binding energy of −11.03 kcal/mol. Molecular Dynamics (MD) simulations were further done to check the stability of MR-taraxerol complex to unravel the structure activity relationship of taraxerol. Furthermore, SAR studies show that taraxerol had the highest degree of molecular similarity (0.78% - 0.93%) with reported antihypertensive oleanane triterpenoids highlighting its efficacy. Conclusion: Our findings corroborate taraxerol as a potential anti-hypertensive agent and leads to the hypothesis of its specificity towards Mineralocorticoid receptor than other receptors in RAAS.